Environmental and nursing-staff factors contributing to aggressive and violent behaviour of patients in mental health facilities - Evalina van Wijk; Annalene Traut; Hester Julie (AOSIS, 2014)
Background: Aggressive and violent behaviour of inpatients in mental health facilities disrupts the therapeutic alliance and hampers treatment. Objectives: The aim of the study was to describe patients' perceptions of the possible environmental and staff factors that might contribute to their aggressive and violent behaviour after admission to a mental health facility; and to propose strategies to prevent and manage such behaviour. Research design: A qualitative, phenomenological study was utilised, in which purposefully sampled inpatients were interviewed over a six-month period. Inpatients were invited to participate if they had been admitted for at least seven days and were in touch with reality. Method: Forty inpatients in two mental health facilities in Cape Town participated in face-to-face, semi-structured interviews over a period of six months. Tesch's descriptive method of open coding formed the framework for the data analysis and presentation of the results. Trustworthiness was ensured in accordance with the principles of credibility, confirmability, transferability and dependability. Results: Analysis of the data indicates two central categories in the factors contributing to patients' aggressive and violent behaviour, namely, environmental factors and the attitude and behaviour of staff. Conclusion: From the perspective of the inpatients included in this study, aggressive and violent episodes are common and require intervention. Specific strategies for preventing such behaviour are proposed and it is recommended that these strategies be incorporated into the in-service training programmes of the staff of mental health facilities. These strategies could prevent, or reduce, aggressive and violent behaviour in in-patient facilities.